STUDI PERENCANAAN PENANGGULANGAN BANJIR KOTA KUALA TUNGKAL KAB. TANJUNG JABUNG BARAT PROPINSI JAMBI - Rinal A.M.K Ginting (Universitas Batanghari Jambi, 2015)
Floodis a natural phenomenon, flood problems caused byebb and flow ofthe oceanortidal wateris one of them. The location of a region that is in direct contact with these a willexperience it. It is see nin the area of Kuala Tungkal District of Tanjabbar. The solutions of fered to over come the flood tideis with the planning system by building in filtration pond sand drainage trunk city center.Judging from the tidesan drain fall, based on thereview of the literature regarding flooding, drain age system sand analysis of rain fall data, the results obtained in the form ofthe dimensions of the parent with extensive drainage channelhy draulic channel cross section72.457m2, 6mhigh, 12 m wide with an area field trunk 64.08km2 discharge planthat flows16.31m3/sec. Farm buildings planned form easuring the water levelof 1.3m, the channel widthof 40 manda length of 80m. The number off arm buildings that can be builtas many as36 pieces. Decreased water discharge that occurs in the Pengabuan riverresultis 3%.Keywords: flood, drainage channel parent Central, building the embankment